A chemo-mechanical model coupled with thermal effect on the hollow core–shell electrodes in lithium-ion batteries - Hu, B.; Ma, Z.; Lei, W.; Zou, Y.; Lu, Chunsheng (2017)
Electrode is a key component to remain durability and safety of lithium-ion (Li-ion) batteries. Li-ion insertion/removal and thermal expansion mismatch may induce high stress in electrode during charging and discharging processes. In this paper, we present a continuum model based on COMSOL Multiphysics software, which involves thermal, chemical and mechanical behaviors of electrodes. The results show that, because of diffusion-induced stress and thermal mismatch, the electrode geometry plays an important role in diffusion kinetics of Li-ions. A higher local compressive stress results in a lower Li-ion concentration and thus a lower capacity when a particle is embedded another, which is in agreement with experimental observations.